Ethical Supervision of Judges to Improve the Integrity of the Constitutional Court - Rozana Sukma Dewi; Avien Zakaria; Aghnia Safana Ilmi (CV. Pustaka Parawali, 2024)
This study aims to analyze the juridical implications of the Constitutional Court Decision Number 90/PUU-XXI/2023 on the independence of Constitutional Court judges. To examine the urgency of regulating the ethical supervision of Constitutional Court judges. This research is expected to be material for improving the law related to the supervision of the ethics of the Constitutional Court judges. The type of research is normative legal research. The approach methods used are the types of statutory approaches, case approaches, and conceptual approaches. The technique of collecting legal materials used is a literature study. The data analysis method used is qualitative descriptive. The deductive method of concluding is used. The results of this study show that the juridical implications of the Constitutional Court Decision Number: 90/PUU-XXI/2023 on the independence of Constitutional Court judges are defects that lead to violations of the code of ethics by Constitutional Court judges during the trial process of the decision, resulting in the loss of the independence of Constitutional Court judges, and the issuance of 4 MKMK decisions. This signals that supervision in judicial institutions such as the Constitutional Court has not been optimal. The urgency of regulating the supervision of the ethics of constitutional court judges is that internal supervision in judicial institutions such as the Constitutional Court has not been optimal. Therefore, it is necessary to reorganize the supervision system and institutional management of the Constitutional Court both internally and externally.